Hubungan Kualitas Relasi Ayah-Anak dengan Kecerdasan Emosional pada Remaja - Siti Hafizhah Rahmah; Arneliwati; Reni Zulfitri (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
The quality of the father-child relationship is related to the adolescent’s emotional intelligence, especially when facing the challenges of physical and emotional development during adolescence. This research aims to determine the relationship between the quality of the father-child relationship and emotional intelligence in adolescents. This research method is a quantitative descriptive correlation with the cross-sectional approach. The research was conducted at SMAN 2 Rengat with 129 respondents using a purposive sampling technique. The analysis used was univariate analysis with frequency distribution and bivariate analysis using the Spearman rank correlation statistical test. The results of the univariate analysis showed that the majority of respondents were in the 16-year age range (68.2%), female (51.2%), had high-quality father-child relationships (34.1%), and had moderate emotional intelligence (34.9%). The bivariate analysis results using the Spearman rank correlation statistical test found a significance level of 0.000 with a correlation coefficient of 0.598. This research concludes that the quality of the father-child relationships has a positive significant relationship with emotional intelligence in adolescents, meaning that the higher the quality of the father-child relationship, the higher the emotional intelligence in adolescents. Fathers and adolescent children can build and maintain a quality relationship to support the adolescent's emotional intelligence.